Food availability to an Adamussium bed during the austral Summer 1993/94 (Terra Nova Bay, Ross Sea) - ALBERTELLI G.; R. CATTANEO VIETTI; A. PUSCEDDU; M. FABIANO; CHIANTORE, MARIACHIARA (Elsevier BV:PO Box 211, 1000 AE Amsterdam Netherlands:011 31 20 4853757, 011 31 20 4853642, 011 31 20 4853641, EMAIL: nlinfo-f@elsevier.nl, INTERNET: http://www.elsevier.nl, Fax: 011 31 20 4853598, 1998)
In the framework of the ROSSMIZE Project Ross Sea Marginal Ice Zone Ecology. of the Italian Antarctic Research Programme PNRA., the organic matter flux through the water column and its role on benthic communities have been taken in particular account. During the austral Summer 1993–1994, from December 27, 1993 to February 11, 1994, a study on this flux in shallow waters was carried out, in a station close to Terra Nova Bay Italian base Ross Sea., at 40 m depth. This site is characterized by the filter-feeding Adamussium colbecki, a scallop which reaches high values of density 60 indrm2. and biomass 120 g DWrm2. At the beginning of the sampling period, a sediment trap was positioned on the sea-bottom and samples were collected every 3–5 days, as well as temperature, salinity and fluorescence data from sea surface to bottom. Fluorescence profiles put in evidence a phytoplankton bloom occurring during the maximum water column stratification, in the last decade of January. Organic matter flux through the water column showed rather constant values up to the 24th of January. Immediately after, a sudden increase took place 24–29 January., reaching 13.55 grm2rd for TSM, 0.24 grm2rd for lipids, 0.53 grm2rd for proteins, 0.37 grm2rd for carbohydrates, 0.69 grm2rd and 0.1 grm2rd for POC and PON, respectively, 0.5 and 2.8 mgrm2rd for chlorophyll-a and phaeopigments, in correspondence to the fluorescence peak occurring in the same period. A large part of the total flux was represented by oval faecal pellets, as accounted by microscopical observations of sedimented material. Most of the pellets were 200–300 mm long, filled mainly by diatom frustules.